Remarkable characterization and determination of atypical E. coli O157 none producing shiga toxin which can produce cytopathic effect on Vero cell and diarrhea in mice - MOSHIRI, M.; TAHAMTAN, Y.; NAMAVARI, M. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study focused on the cytopathic effect of an unusual form of E. coli O157:H7 (atypical E. coli O157 (a-O157)) on Vero cell and infant mice. Multiplex PCR assay showed that they did not carry the gene for either shiga toxin 1 (stx1) or stx2 and other virulence factors. Increased changes in epithelial cell morphology, inter and intracellular gap junction and invading were assessed using Vero assay. In addition, a-O157infection causes disruptions of intercellular tight junctions, leading to clinical sequelae that include acute diarrhea in mice. Vero cell monolayers were exposed to a-O157influx and disintegrated tight junction of Vero cell line. Infected Vero cell enhance the number of attaching and effacing (A/E) lesions. Collectively, these findings provide in vitro evidence that Vero cell infected by a-O157was shown injury in epithelial cell barrier and induced A/E lesion the same as E. coli O157:H7 stx positive. These variants cannot be diagnosed by routine monitoring methods like biochemical assay for E. coli O157:H7 stx positive control. Finally, the data suggest that not only typical but also a-O157are an important cause of diarrhea in mice and produce cytopathic effect on Vero cell and may be harmful for food animal and also human.